A Comprehensive Systematic Literature Review on Opportunities, Challenges, and Implementation Strategies of Artificial Intelligences for Indonesian Primary Schools - Insany, Arie; Suhandi, Andi; Gunari, Gun Gun Ahmad (International Conference on Elementary Education, 2024)
This study, employing a systematic literature review (SLR) of nine carefully selected studies from an initial pool of 180 on Google Scholar, investigates the benefits and challenges of using Artificial Intelligence (AI) in primary education, particularly for making recommendation for the Indonesian context. Utilizing the PRISMA 2020 framework for selection, the research highlights AI’s potential to revolutionize education by personalizing learning experiences, enhancing pedagogical methods, and improving assessment and administrative efficiencies. However, it also identifies significant challenges, including concerns about academic integrity, ethical and privacy issues, and the digital divide. Crucially, the study offers targeted recommendations for the effective implementation of AI in Indonesian primary schools, emphasizing the need for equitable technology access and comprehensive teacher training. These recommendations aim to mitigate the challenges while maximizing the benefits, thereby facilitating a more adaptive, inclusive, and forward-looking educational environment. This study provides valuable insights for policymakers and educators, underlining the importance of a strategic approach in integrating AI into primary education systems.